PENGARUH LATIHAN INTERVAL RUNNING TERHADAP KECEPATAN LARI SSB RUMBAI PRATAMA U-14 PEKANBARU - Aryefta, Yolanda Permadito; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research Problems can be formulated as the following "Whether there is influence of interval exercise running against running speed on SSB Tassel Pratama U-14 Soweto" in this study, researchers used a One-Group research design Pretest-Posttest Design, where in the design of this pretest before there is sufficient given the treatment and after treatment given postest, population research is the generalization of the object/subject who has the qualities and characteristics certain specified leh researchers to learn and then drawn the conclusion (Sugiyono, 2010:90). The population in this research is the SSB Tassel Pratama U-14 Soweto amounted to 13orang in this study, researchers collected data by means of test, measurement and observation. Pre test (preliminary test) test is beginning as a reference for research. These initial tests are usually done before a meeting at all. Post test (final test) Tests carried out after the end of treatment for 16 times it has done. After 16 times, then researchers will hold a similar final tests initial tests i.e. took the data as test data between the influence of initial and final test. Then after that conclusion can be withdrawn if there is an increase in the latihan done over or not. The data obtained were analyzed in a descriptive, then subsequent hypothesis testing conducted research that has been filed in compliance issues, namely: "there is the influence of the Interval Workout runnings (X) against the increase in running speed (Y). Based on the analysis performed, the values between the beginning and end of the test the test workout Interval running against significant levels in speed with 0.05 with degrees of freedom N – 1 (12) this indicates that the value (8.66) (1.782) can thus be It was concluded that the hypothesis stating There the influence of the Interval Workout running (X) against running speed on SSB Tassel Pratama U14 Pekanbaru (Y) on the SSB Tassel Pratama U-14 Pekanbaru.Keywords: Running Against running speed SSB Tassel Pratama U-14 Pekanbaru